Human and predator presence shape diel activity of urban red squirrels - Drenske, Sinah; Louvrier, Julie; Grabow, Marius; Landgraf, Conny; Kramer-Schadt, Stephanie; Planillo, Aimara (Frontiers in Ecology and Evolution, 2024)
In urban areas, wildlife has to adapt to human presence and novel predators such as pet species, including the altered conditions of the environment. In such novel settings, the timing of activity is crucial to minimize the risk of mortality. To do so, species may reduce total activity time by increasing activity peaks at specific moments or shifting activity times. We analyzed camera trap data from a citizen science project over four project phases, including spring and autumn before and during the SARS-CoV-2 lockdown, to understand the effects of human, pet (cat, dog), and predator (marten) presence on the activity patterns of urban red squirrels (Sciurus vulgaris; hereafter ‘squirrel’). We examined squirrel activity at seasonal and hourly resolutions in relation to human, garden, urban, and predator factors. We considered human presence as both a direct effect of lockdown and an indirect disturbance measured through urban variables. Results show that direct human presence during lockdown increased squirrel activity intensity in both seasonal and hourly patterns without reducing total activity time. Predator presence affected timing of activity, decreasing total daily activity. Pets, like cats, decreased activity at both resolutions, while martens had a limited effect detected only at the hourly resolution. During lockdown, squirrels may have increased their activity in gardens due to more anthropogenic resources (food or nesting material), but constant threats from pets force them to avoid certain areas despite the benefits. This highlights the delicate balance squirrels must maintain in adapting to human-altered environments while managing predation risks.